Análise comparativa entre a fecundidade de Dilocarcinus pagei Stimpson e Sylviocarcinus australis Magalhães & Turkay (Crustacea, Decapoda, Trichodactylidae) no Pantanal do Rio Paraguai, Porto Murtinho, Mato Grosso do Sul - Mansur, Cynthia de Barros; Hebling, Nilton José [UNESP] (Sociedade Brasileira de Zoologia, 2002)
The aim of this study was to estimate the fecundity of Dilocarcinus pagei Stimpson, 1861 and Sylviocarcinus australis Magalhães & Turkay, 1996, collected in the Paraguay River, Porto Murtinho County, State of Mato Grosso do Sul, Brazil, between coordinates 21º42,000'S 57º33,649'W and 21º41,449'S 57º33,770'W, in the period of April 1999 to March 2000. After general collection procedures, the specimens were measured and processed in laboratory conditions. The river water crab species hatch like juveniles and, frequently, female specimens were observed carrying eggs in different stages of development, besides juveniles and eggs at the same time. It was apparent in the frequency distributions that D. pagei has a carapace width average greater than S. australis. The number of eggs and juveniles transported varied amongst species and amongst size class. A size superposition was observed between young and adult females for both species. According to the calculated fecundity index, D. pagei presented slightly more elevated values (7.41) than S. australis (6.65). Eggs are spherical and are not adhering to pleopods. Egg size did not varied during development, continuing with 2mm diameters.
Comparative analysis of fecundity between Dilocarcinus pagei Stimpson and Sylviocarcinus australis Magalhães & Turkay (Crustacea, Decapoda, Trichodactylidae) in the Pantanal region of Paraguay River, Porto Murtinho, Mato Grosso do Sul
Keywords: Dilocarcinus pagei; Sylviocarcinus australis; fecundity; Trichodactylidae; Pantanal